Relationship between Eco-Efficiency with Asset Value and Returns of Corporations Listed in Tehran Stock Exchange - Younes Badavar Nahandi (Shahid Bahonar University of Kerman, 2012)
This research examines the relationship between corporate eco-efficiency and financial performance. A database has been created for environmental and financial information of the selected corporations in which eco-efficiency of the corporations has been determined, using 11 eco-efficiency measures, and firm’s value and asset return have been regarded as financial performance measures. Statistical population of the research consists of the companies listed in Tehran Stock Exchange (TSE), and sampling has been done using systematic deletion method. Data analysis has been carried out, using correlation and regression tests. The results of hypotheses tests indicate that there is no significant relationship between eco-efficiency and financial performance measures.